2010
DOI: 10.1074/jbc.m110.145813
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous SNAP-25 Regulates Native Voltage-gated Calcium Channels in Glutamatergic Neurons

Abstract: In addition to its primary role as a fundamental component of the SNARE complex, SNAP-25 also modulates voltage-gated calcium channels (VGCCs) in various overexpression systems. Although these studies suggest a potential negative regulatory role of SNAP-25 on VGCC activity, the effects of endogenous SNAP-25 on native VGCC function in neurons are unclear. In the present study, we investigated the VGCC properties of cultured glutamatergic and GABAergic rat hippocampal neurons. Glutamatergic currents were dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 43 publications
4
54
0
Order By: Relevance
“…Consistently, silencing endogenous SNAP-25 results in increased VGCC activity in glutamatergic neurons [8,9].…”
Section: Introductionmentioning
confidence: 60%
“…Consistently, silencing endogenous SNAP-25 results in increased VGCC activity in glutamatergic neurons [8,9].…”
Section: Introductionmentioning
confidence: 60%
“…Our data so far suggest that SNAP-25 reductions affect the localization and/or stabilization of PSD-95 in dendritic protrusions, influencing synapse organization and strength during development and plasticity. Consistent with this possibility, acute downregulation of SNAP-25 expression by siRNA, 10 To investigate whether SNAP-25 controls the latter processes via its SNARE function, neurons were transfected with 45; Mann-Whitney rank-sum test P ≤ 0.001; 3 independent experiments). The decrease in mature spine number (mushroom-type) is accompanied by an increase in thin spine number (filopodia-like) (number of mushroom spines per micron, wt: 0.31 ± 0.02, number of examined dendrites: 63; number of neurons: 37; Het: 0.16 ± 0.01, number of examined dendrites: 84; number of neurons: 45; number of filopodia-like spines per micron, wt: 0.06 ± 0.01; Het: 0.11 ± 0.01; Mann-Whitney rank-sum test P ≤ 0.001;a cDNA codifying for the BonT/E light chain, which cleaves SNAP-25 at its N-terminal side and prevents the protein entering the fusion complex.…”
Section: Resultsmentioning
confidence: 95%
“…56 By taking advantage of mixed cultures of wt and Het neurons, we demonstrated that postsynaptic defects in In recent years SNARE/SM proteins have been shown to be involved in activity-dependent AMPA receptor exocytosis during LTP 22 and SNAP-25, in particular, has been reported to have a role in the removal of kainate receptors from the postsynaptic membrane, 57 in the insertion of NMDA receptors in neuronal plasma membrane 21 and of P/Q and L typevoltage gated calcium channels. 10,58 Also, acute regulation of SNAP-25 expression has been found to impair synaptic plasticity probably affecting NMDAR trafficking. 22 Our data indicate that SNAP-25 has also a structural role in the postsynaptic compartment by interacting with the postsynaptic protein p140Cap, which in turn binds to PSD-95.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations